The impact of VEGF on cancer metastasis and systemic disease - Yunlong Yang; Yihai Cao (2022)
Metastasis is the leading cause of cancer-associated mortality and the underlying mechanisms of cancer metastasis remain elusive. Both blood and lymphatic vasculatures are essential structures for mediating distal metastasis. The vasculature plays multiple functions, including accelerating tumor growth, sustaining the tumor microenvironment, supplying growth and invasive signals, promoting metastasis, and causing cancer-associated systemic disease. VEGF is one of the key angiogenic factors in tumors and participates in the initial stage of tumor development, progression and metastasis. Consequently, VEGF and its receptor-mediated signaling pathways have become one of the most important therapeutic targets for treating various cancers. Today, anti-VEGF-based antiangiogenic drugs (AADs) are widely used in the clinic for treating different types of cancer in human patients. Despite nearly 20-year clinical experience with AADs, the impact of these drugs on cancer metastasis and systemic disease remains largely unknown. In this review article, we focus our discussion on tumor VEGF in cancer metastasis and systemic disease and mechanisms underlying AADs in clinical benefits.